Phycocyanin Extraction from Spirulina platensis and Its Antimalarial Activity In-Vitro - Diah Anggraini Wulandari; Iriani Setyaningsih; Din Syafrudin; Puji Budi Setia Asih (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Phycocyanin is a pigment-protein complex from the light-harvesting phycobiliprotein family which isoften found in cyanobacteria. The product phycocyanin produced by phanizomenon flos-aquae and Spirulinasp. The aim of this study were to determine the best solvents purification phycocanin from Spirulina platensisin three solvents, phosphate buffer, water and aceton ammonium sulphate and to evaluate the antimalarialactivity in vitro of phycocyanin in the best solvent extraction from S. platensis. The method of this study wasusing in-vitro antimalarial method. The result showed C- phycocyanin (C-PC), yield, and protein contentsof phycocyanin were 8 mg/mL, 20.22%, 1.88% extracted and purified by phosphate buffer, 6.63 mg/mL,16.58 %, 3.51% extracted and purified by water, 2.86 mg/mL, 7.15%, 8.4% extracted and purified by acetoneammonium sulphate respectively. Phosphate buffer was the best solvent of phycocyanin extraction from S.platensis. Antimalarial activity in vitro of phycocyanin in hosphate buffer against Plasmodium falciparumstrains 3D7 with IC50 was 158,489 μg/mL. The possible mechanism might be relied on the destruction ofpolymerization of Haemozoin by binding of C-PC with ferriprotoporphyrin-IX at the water surface of theplasma membrane.